Crime radiation theory: the co-production of crime patterns through opportunity creation and exploitation - Shannon J. Linning; Kate Bowers; John E. Eck (Crime Science)
Abstract Considerable research shows that crime is concentrated at a few proprietary places: addresses and facilities. Emerging research suggests that proprietary places may radiate crime: activities at a place increase the risk of crime in the area around it. Weaknesses in the research create uncertainty about radiation, so we need more rigorous research. To conduct this research, we need a theory of crime radiation that operates at two spatial levels: the proprietary place and the area. This paper describes such a theory. Our theory states that crime radiation stems from the interaction between place management decisions at the place and offenders searching for opportunities in the area. Place managers create crime opportunities inside and outside their places. Offenders exploit place managers’ creations by deliberately searching for opportunities or by chancing upon the opportunities. The ways place managers and offenders interact gives rise to three types of crime radiation: hot dot, veiled dot, and cold dot. Finally, we propose questions crime scientists should answer to better understand crime radiation.